Aktivitas Peredaman Radikal ABTS (2,2'-azino-bis(3 - ethylbenzothiazoline-6-sulfonic acid)) oleh Ekstrak Etanol Kulit Nanas Madu (Ananas comosus L.Merr) - Kusumawati, Dwi Endah; Chaqi, Muhammad Dhiya’ul (Sultan Agung Islamic University of Semarang, 2026)
Background: Free radicals trigger various degenerative diseases, making the exploration of natural antioxidants essential. Honey pineapple (Ananas comosus L.) peel, often considered agricultural waste, contains bioactive compounds such as phenolics and flavonoids with potential antioxidant activity. This study aims to quantify the antioxidant activity of honey pineapple peel ethanolic extract, expressed as the IC₅₀ value. Methods: Honey pineapple peel powder was macerated using 70% ethanol. The antioxidant activity was evaluated using the ABTS cation radical assay. Extract concentrations (10, 20, 30, 40, and 50 µg/mL) were mixed with ABTS solution, and absorbance was measured at 747 nm using a UV-Vis spectrophotometer. Results: The IC₅₀ value for Vitamin C was 6.173 µg/mL, whereas the honey pineapple peel extract yielded an IC₅₀ of 61.476 µg/mL. This indicates that the antioxidant potency of the extract is 9.958 times lower than that of Vitamin C. Conclusion: The ethanolic extract of honey pineapple peel exhibits antioxidant activity with an IC₅₀ of 61.476 µg/mL. Since the inhibition percentages within the tested range did not reach 50%, this value was determined through linear regression extrapolation. Future studies should employ higher concentration ranges to confirm the inhibitory effectiveness.